OPTIMALISASI PENUGASAN KARYAWAN PADA UMKM BENGKEL SEPEDA MOTOR DI SEMARANG DENGAN MENGGUNAKAN PROGRAM PERANGKAT LUNAK MANAJEMEN KUANTITATIF â€œPOMâ€ - Imam Nuryanto; Ida Farida (MEDIA, 2014)
This study was conducted to determine the assignment of employees. SMEs must have a sustainable competitive advantage, efforts can be achieved is an optimal assignment of employees Problems occur when this is not optimal assignment method of employees, so that the necessary applied research on SMEs to resolve the problem of employee assignment. From the results obtained by analysis of the facts, there are many SMEs are not optimal in the assignment of employees, in terms of value assignment small when compared with the value of the assignment of the software, so it requires some changes in the assignment of employees to be optimal. With the optimal assignment of SMEs can improve sustainable competitive advantage (competitiveness).